Technological procedures in health information systems: Country collaboration and term co-occurrence analysis - Araujo Inastrilla, Carlos Rafael; Gutiérrez Vera, Dayami; Llosa Santana, Mayelin; Vitón Castillo, Adrián Alejandro; Araujo Inastrilla, Alejandro; Manzanet Valladares, Katherine (Iberoamerican Journal of Science Measurement and Communication, 2024)
An analysis of collaboration between countries and the co-occurrence of terms is presented in the context of technological procedures in Health Information Systems (HIS). The scientific production indexed in Scopus on technological procedures in the SIS is examined, addressing 481 publications from 1980 to 2023. The study reveals the existence of regional groups of countries that tend to collaborate more closely with each other, as well as areas of improvement and opportunity in collaboration between countries from different regions and levels of development. The importance of technology and health as transversal and key elements in the HIS is highlighted and greater collaboration between diverse countries is suggested to democratize health information management and monitoring procedures to ensure the quality of health information. The article provides a comprehensive view of the trends and areas of interest in the field of study to contribute to advancing and continuously improving technological procedures in HIS.